Seeding the galactic centre gas stream: gravitational instabilities set the initial conditions for the formation of protocluster clouds - Henshaw, Jonathan D.; Longmore, Steven N.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society. Letters, 2016)
Star formation within the Central Molecular Zone (CMZ) may be intimately linked to the orbital dynamics of the gas. Recent models suggest that star formation within the dust ridge molecular clouds (from G0.253+0.016 to Sgr B2) follows an evolutionary time sequence, triggered by tidal compression during their preceding pericentre passage. Given that these clouds are the most likely precursors to a generation of massive stars and extreme star clusters, this scenario would have profound implications for constraining the time-evolution of star formation. In this Letter, we search for the initial conditions of the protocluster clouds, focusing on the kinematics of gas situated upstream from pericentre. We observe a highly regular corrugated velocity field in {l, vLSR} space, with amplitude and wavelength A = 3.7 ± 0.1 km s−1 and λvel,i = 22.5 ± 0.1 pc, respectively. The extremes in velocity correlate with a series of massive (∼104 M⊙) and compact (Req ∼ 2 pc), quasi-regularly spaced (∼8 pc), molecular clouds. The corrugation wavelength and cloud separation closely agree with the predicted Toomre (∼17 pc) and Jeans (∼6 pc) lengths, respectively. We conclude that gravitational instabilities are driving the condensation of molecular clouds within the Galactic Centre gas stream. Furthermore, we speculate these seeds are the historical analogue of the dust-ridge molecular clouds, representing the initial conditions of star and cluster formation in the CMZ.